665 Effect of asbestos on foxp3 expression in human t cell line mt-2. (24th April 2018) - Matsuzaki, H; Lee, S; Maeda, M; Kumagai-takei, N; Yoshitome, K; Nishimura, Y; Otsuki, T
Abstract : Introduction: Asbestos fibres cause mesothelioma and lung cancer. We propose that asbestos suppress anti-tumour immune system in addition to transformation of mesothelial and lung epithelial cells. It is considered that regulatory T cells, Treg produce inhibitory cytokines to suppress immune reaction against tumour cells. We employed human T cell line MT-2 cell as a model of Treg and cultured them with low concentration of asbestos for 8 months. MT-2 cells exposed with low-concentration asbestos for long term showed higher viability after treatment with high lethal dose of asbestos than original MT-2 cells, and they were designated as MT-2Rst. However, it is still unclear how asbestos induces apoptosis in MT-2 cells and molecular basis of resistance of MT-2Rst cells to high concentration of asbestos. Recently, we found that forkhead transcription factor FoxP3 plays an important role in regulation of apoptosis induced by asbestos. Methods: We analysed the regulation of FoxP3 transcription in MT-2Org and MT-2Rst cells using luciferase reporter plasmids containing promoter sequence of FoxP3 gene. Result: There was no significant difference in FoxP3 reporter activity between MT-2Org and MT-2Rst cells. Discussion: Our result indicates that long-term exposure with asbestos suppressed FoxP3 transcription through the epigenetic modification, such as DNA methylation.